2018
DOI: 10.1099/jmm.0.000826
|View full text |Cite
|
Sign up to set email alerts
|

Resistance pattern and distribution of carbapenemase and antiseptic resistance genes among multidrug-resistant Acinetobacter baumannii isolated from intensive care unit patients

Abstract: Our study revealed the high frequency of multidrug- and carbapenem-resistant isolates of A. baumannii in ICU patients, with a high prevalence of the genes blaOXA-23 and blaOXA-51. However, no apparent biocide resistance was seen in A. baumannii isolates. It appears that appropriate surveillance and control measures are essential to prevent the emergence and transmission of MDR A. baumannii in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
5
25
1
2
Order By: Relevance
“…According to our previous study [2], all A. baumannii isolates were resistant to three or more antimicrobial agents and considered as MDR. The highest rate of resistance was detected against ciprofloxacin and imipenem (100%), followed by piperacillin (99%) and cefepime/levofloxacin/ceftazidime (97%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our previous study [2], all A. baumannii isolates were resistant to three or more antimicrobial agents and considered as MDR. The highest rate of resistance was detected against ciprofloxacin and imipenem (100%), followed by piperacillin (99%) and cefepime/levofloxacin/ceftazidime (97%).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, a total of 100 non-replicate A. baumannii clinical isolates were randomly recovered from different specimens including blood, sputum, wound swabs, chest tube secretions and urine from immunocompromised patients with symptomatic clinical infections at least 48 h after ICU admission [2]. Case patients were defined as patients infected by A. baumannii according to the Centers for Disease Control and Prevention criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, SENTRY Antimicrobial Surveillance Program reported the highest number of MDR strains of A. baumannii in Europe and Latin America, Asia-Pacific, and North America between 1997 and 2016 (24). Also, high prevalence of MDR A. baumannii has emerged as a serious problem in healthcare settings in Iran (25). Previous studies have shown that fluoroquinolones are one of the first-line therapies for A. baumannii infections (26).…”
Section: Discussionmentioning
confidence: 99%